Development of Children's Moral Intelligence According to al-Ghozali - Izza, Yogi Prana; Azmi, Ahmad Rifqi; Fauzi, Mohammed Suhaimi Mohamed (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This research aims to explain the moral development of children according to al-Ghozali. Al-Ghozali as a Muslim philosopher has his views. This research is vital because child delinquency that is currently occurring, such as committing abuse and murder, can be categorized as a criminal act. One of the causes of delinquency is the weak distinction between goodness (al-khair) and evil (al-syar) as a fundamental moral principle. This research uses a qualitative approach with the type of library research. The data consists of the writings of al-Ghozali as the figure studied, books that study al-Ghozali's moral thinking, and scientific journals that discuss moral intelligence. The collected data was then analyzed using the content analysis method. The research results explain that motivation for intelligent morals is based on the spirit of religion, namely happiness in this world and the hereafter, and the measure of good and evil is not only the mind and heart but also the Shari'a. All children have the potential to be morally intelligent with the determining factors being education and family, not genetics. There are four virtues (fadhilah) which are the main aspects in developing children's intelligence through the concept of a